(untitled) (Fiep Bulletin - online, 2017)
This article aims to offer Physical Education Professionals and especially those who act as Technical Director, theknowledge necessary to exercise this activity that requires high professional training and strict adherence to ethics; to this end, weseek to carry out a study axiological, teleological and systematic of the law that regulated profession and thus minimize civil andcriminal charges of RTs.